On Maximal and Minimal Fuzzy Sets in I-Topological Spaces - Samer Al Ghour (International Journal of Mathematics and Mathematical Sciences)
The notion of maximal fuzzy open sets is introduced. Some basic properties and relationships regarding this notion and other notions of I-topology are given. Moreover, some deep results concerning the known minimal fuzzy open sets concept are given.